2019
DOI: 10.1002/mnfr.201900404
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Chain n‐3 PUFA Content and n‐6/n‐3 PUFA Ratio in Mammal, Poultry, and Fish Muscles Largely Explain Differential Protein and Lipid Oxidation Profiles Following In Vitro Gastrointestinal Digestion

Abstract: Scope Muscle food characteristics (fatty acid profile, heme‐Fe, intrinsic antioxidants) that relate to the formation of (patho)physiological oxidation products during gastrointestinal digestion are investigated. Methods and Results Muscles (n = 33) from 18 mammal, poultry, and fish species, of which some are mixed with lard to standardize their fatty acid profile, are digested in vitro. Lipid oxidation is assessed by thiobarbituric reactive substances (TBARS), n‐3 PUFA derivative 4‐hydroxy‐2‐hexenal and propan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 58 publications
4
29
3
Order By: Relevance
“…Although those differences were not signi cant in all compared groups, apparently they contributed to different extent of lipid oxidation. On the contrary, Van Hecke et al [7] concluded the n-6 to n-3 ratio correlated more with PUFA oxidation than did the absolute content of PUFA, which was not con rmed in our study. Moreover, rearing conditions affect animal welfare and, consequently, the level of preslaughter stress and meat quality [13].…”
Section: Lipid and Protein Oxidation Of Meatcontrasting
confidence: 99%
See 4 more Smart Citations
“…Although those differences were not signi cant in all compared groups, apparently they contributed to different extent of lipid oxidation. On the contrary, Van Hecke et al [7] concluded the n-6 to n-3 ratio correlated more with PUFA oxidation than did the absolute content of PUFA, which was not con rmed in our study. Moreover, rearing conditions affect animal welfare and, consequently, the level of preslaughter stress and meat quality [13].…”
Section: Lipid and Protein Oxidation Of Meatcontrasting
confidence: 99%
“…In our study, the recommended PUFA to SFA ratio was achieved in breasts and thighs of all experimental groups (from 0.91 to 1.07). However, in the current study, the ratio of n-6 to n-3 PUFA was several times greater than recommended (it was from 19.70 to 20.71) and determined in other studies [7,8,10,11,41]. This imbalance in the n-6 to n-3 PUFA ratio determined in our study was a consequence of diet, based mainly on maize and soybean that contained high levels of linoleic acid (n-6 fatty acid), and insu cient quantities of feeds that were sources of n-3 fatty acids.…”
Section: Fatty Acid Pro Le Of Meatcontrasting
confidence: 73%
See 3 more Smart Citations